Appearance of Heterogeneous Macrophages During Development of Isoproterenol-Induced Rat Myocardial Fibrosis. (July 2021) - Koga, Masaaki; Karim, Mohammad Rabiul; Kuramochi, Mizuki; Izawa, Takeshi; Kuwamura, Mitsuru; Yamate, Jyoji
Macrophages appearing in lesions are polarized toward M1 (for inflammation) and M2 (for anti-inflammation/fibrosis) types. We analyzed immunophenotypes of macrophages appearing in myocardial lesion in rats injected once with isoproterenol (10 mg/kg body weight). Inflammation following myocardial necrosis on day 1 was seen with a peak on days 3 and 5, and thereafter, reparative fibrosis developed on days 7 to 28. CD68 + M1 macrophages were seen in the early stages of injury and inflammatory on days 1 to 7, and thereafter, CD163 + M2 macrophages increased in the late stages of fibrosis on days 7 to 28. There was the polarization of M1 and M2 macrophages. The kinetics of macrophages reacting to Iba-1 and Galectin-3 was similar to that of M1 macrophages, indicating that Iba1- and Gal-3-positive macrophages might have functions of M1 type. Double immunofluorescence revealed that CD204- and MHC class II-positive macrophages are polarized toward M1 and M2 types, respectively. CCR2 messenger RNA expression is transiently elevated on day 1. Since CCR2 is a marker of blood monocytes, M1 macrophages might be recruited from blood monocytes. Collectively, macrophages expressing heterogeneous immunophenotypes participate in myocardial fibrosis. These findings would be useful for understanding the pathogenesis of myocardial fibrosis and analyzing myocardial toxicity.